Energy and performance analysis of a turbofan engine with the aid of dynamic component efficiencies - Cihangir, Serhan Ahmet; Aygun, Hakan; Turan, Onder (Pergamon-Elsevier Science Ltd, 2022)
Assessment of performance of turbofan engine with different design parameters is crucial for meeting the per-formance requirements by considering each key components of the engine. To comprehend influences of component efficiencies to mitigate environmental effect from turbofans has been hot topics in aviation field recently. In this study, firstly, impacts of polytropic efficiencies of fan, compressor and turbine as well as pressure ratio of combustor (CPR) on several turbofan performance are dealt with at several flight conditions. Secondly, it is tried to show difference of performance metrics under ideal and real conditions. The discrepancy between performance parameters computed at ideal and real cases gets relatively high. Namely, at take-off condition, the difference between ideal and real specific fuel consumption is computed as 29.12% whereas it is found as 28.37% at cruise condition, which shows that considering the system as ideal makes the computations inappropriate for performance analysis. Moreover, performance parameters of turbofan is more sensitive to compressor efficiency compared with turbine. As the polytropic efficiencies of fan and compressor are close to highest, net thrust of the engine develops from 109.05 kN (baseline) to 124.71 kN at take-off while it increases from 26.36 kN (baseline) to 29.27 kN at cruise condition. With effect of the elevated pressure ratio of combustor and efficiency of turbine, thrust of the engine increases to 118.23 kN at take off and to 27.84 kN at cruise condition. Finally, as Mach number increases, the difference between ideal and real performance values sharply increases. Therefore, when analyzing on turbofan engines, the assumptions should be minimum as possible as, otherwise the findings make the engineers to misguide for system optimization. Besides, these outcomes show that if the components with higher polytropic efficiency can be obtained, overall efficiency of turbofan, thereby environmental sustainability could be elevated to upper level compared with baseline.
Keywords: Polytropic efficiency; Turbofan performance; Specific fuel consumption; Overall efficiency